THE HEALING OF BLINDNESS IN APOCRYPHAL BOOKS AND THE FINE ARTS - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The image of Tobit and Tobias in apocryphal books and the fine arts gives the possibility to break a code of the attitude of society to the person having the sight disabilities in contemporary society. We can assume that the image of Tobias which has lots of positive moral features in the development of history could have the influence to the formation of a positive attitude of the society to sightless people. The history of Tobias’s life and especially its happy ending had a great influence on the formation of the image of the guardian angel and the spread in Italian Renaissance pictorial art as well as in the art of other countries starting from the fifteenth century.